PERTUKARAN ION BATUBARA UNTUK MENGURANGI KADAR Na DENGAN MEMANFAATKAN AIR ASAM TAMBANG - Hendri P. Perangin-angin (INTAN Jurnal Penelitian Tambang, 2019)
Coal leaching by using mine acid water and solution Mg2+ can reduce the levels of ash and alkali to its needs grade. Thus demonstrates the ongoing leaching process of ion exchange between the ions contained in coal with ions contained in the solution. Coal can acted as ion exchanger due to its hollow structure that could contained alkali and earth-alkali ions in its cavities. Thus the alkali ions can be exchanged with other ions in solution. Coal have more adsorption affinity to divalent alkali ion such as Mg2+ and Mn2+ compare to monovalent alkali ion such as Na+. For ion with the same charge the ion with smaller volume would be prefer due to the relaxation of matrix contraction within the exchange. The first phase leaching conducted to understand the Na content level trend on coal by comparison to Na solution content. The procedure of the study is as follow: first coal is leached with mine acid water, second the pulp drained and count the Na, Mg, Mn content, and third make the graph using the calculation.